2020
DOI: 10.3390/ph13040073
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of Stilbenes (Piceatannol and Resveratrol) in Passiflora edulis By-Products

Abstract: Recently, studies on the by-products from the food industry, such as passion fruit seeds, have significantly increased, as these can have an added value, due to their properties, such as potential antioxidant activity. This study was conducted to determine the presence of piceatannol and resveratrol in various extracts of passion fruit (Passiflora edulis) seeds from Madeira Island and a commercial passion fruit oil was used as reference. The commercial oil and the extracts that were obtained by traditional Sox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Resveratrol ( Figure 1 ) is a stilbene-based natural polyphenolic compound produced by various plants [ 49 ] belonging to various plant families, for example, Ericaceae , Leguminosae , Liliaceae , Moraceae , Myrtaceae , Pinaceae , Polygonaceae , Rosaceae , and Vitaceae [ 50 , 51 ]. The highest levels of resveratrol were detected in fruits of Vitis vinifera L. [ 52 ], Passiflora edulis L. [ 53 ], Vaccinium macrocarpon Aiton [ 54 ], Vaccinium myrtillus L., Vaccinium vitis-ideae L. var. vitis-ideae , Vaccinium vitis-ideae L. var.…”
Section: General Characteristics Of Plant Phenolics Tested In Preementioning
confidence: 99%
“…Resveratrol ( Figure 1 ) is a stilbene-based natural polyphenolic compound produced by various plants [ 49 ] belonging to various plant families, for example, Ericaceae , Leguminosae , Liliaceae , Moraceae , Myrtaceae , Pinaceae , Polygonaceae , Rosaceae , and Vitaceae [ 50 , 51 ]. The highest levels of resveratrol were detected in fruits of Vitis vinifera L. [ 52 ], Passiflora edulis L. [ 53 ], Vaccinium macrocarpon Aiton [ 54 ], Vaccinium myrtillus L., Vaccinium vitis-ideae L. var. vitis-ideae , Vaccinium vitis-ideae L. var.…”
Section: General Characteristics Of Plant Phenolics Tested In Preementioning
confidence: 99%
“…Such observation is corroborated by Santana et al [4], who confirmed that piceatannol concentration is directly correlated with extraction temperature. More recently, Krambeck et al [34] applied ultrasound-assisted extraction and reported values of around 10 µg of piceatannol/mL extract of PFBP. Similar results were obtained in this work using EtOH at 110 • C (extracts were diluted to 1 mg/mL before injection).…”
Section: Bnohmentioning
confidence: 99%
“…Resveratrol and its analogs are usually found in significant amounts in grapes [52]. Two studies using P. edulis reported trans-resveratrol in ethanolic seed extracts [53] and resveratrol, with the use of acetone extraction assisted by the ultrasound of P. edulis by-products [34]. Other stilbenes identified in this work were classified as piceatannol derivatives, and were recently found in P. edulis by Pan et al [43], named passiflorinol C/D-type isomers, cyperusphenol B, passiflorinol A/B-type isomers, cyperusphenol D, and cassigarol D. The same authors elucidate the potential of such compounds as hypoglycemic agents due to the promising results in α-glucosidase inhibitory activities, where passiflorinol B exhibited the best results, achieving an IC 50 = 1.7 µM.…”
Section: Tentative Identification Of Phenolic Compounds From D-pfbp By Uhplc-q-tof-ms/msmentioning
confidence: 99%
“…Res and Pic are major stilbene compounds that are predominantly present in various natural products, such as sim fruit ( Rhodomyrtus tomentosa ) seeds [ 11 ] and passion fruit ( Passiflora edulis ) seeds [ 12 ]. The molecular structure of Res comprises two aromatic rings connected by a methylene double bond.…”
Section: Introductionmentioning
confidence: 99%